SYNONYMY AND NEW INFORMATION ON SIMULIDAE OF THE NEW WORLD - VARGAS, LUIS (Instituto Politécnico Nacional, Escuela Nacional Ciencias Biología, Laboratorio MicroBiología Experimental, CD MEXICO, DF, MEX, 1944)
The rare mosquito, U syntheta, described by Dyar and Shannon from a single [female] from Texas, is apparently widely distributed in the Mexican tableland (Jalisco, San Luis Potosi), reaching Mexico City, its southern limit, where the author collected > 2
REV SOC MEX HIST NAT
Keywords: SYNONYMY, NEW INFORMATION, SIMULIDAE, NEW WORLD; CIENCIAS DE LA VIDA; BIOLOGIA DE INSECTOS (ENTOMOLOGIA)